2007
DOI: 10.1128/aem.00120-07
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Temporal Postdischarge Decontamination of Bacteria by Gliding Electric Discharges: Application to Hafnia alvei

Abstract: This study aimed to characterize the bacterium-destroying properties of a gliding arc plasma device during electric discharges and also under temporal postdischarge conditions (i.e., when the discharge was switched off). This phenomenon was reported for the first time in the literature in the case of the plasma destruction of microorganisms. When cells of a model bacterium, Hafnia alvei, were exposed to electric discharges, followed or not followed by temporal postdischarges, the survival curves exhibited a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 29 publications
5
82
0
1
Order By: Relevance
“…They proposed the application of the Weibull model to the description of non-thermal plasma inactivation, whereas an empirical model seemed to better describe the obtained triphasic inactivation curves. The GInaFiTtool was successfully applied to microbial inactivation of bacteria and yeast by gliding arc discharges (Kamgang, 2007;Kamgang-Youbi et al, 2007.…”
Section: Modeling Of Inactivation Kineticsmentioning
confidence: 99%
“…They proposed the application of the Weibull model to the description of non-thermal plasma inactivation, whereas an empirical model seemed to better describe the obtained triphasic inactivation curves. The GInaFiTtool was successfully applied to microbial inactivation of bacteria and yeast by gliding arc discharges (Kamgang, 2007;Kamgang-Youbi et al, 2007.…”
Section: Modeling Of Inactivation Kineticsmentioning
confidence: 99%
“…Atmospheric nonthermal plasmas of the gliding-arc type (Glidarc) (9, 25) were found to be efficient against microorganisms for treatments performed under burning discharge (12,13,22,26), and the inactivation of cells in water could continue after the discharge had been switched off (13). Microbial cells were also killed by contact with water that had first been activated by discharges (and so-called plasma-activated water [PAW]) without being themselves subjected to the plasma plume (14, 15).…”
mentioning
confidence: 99%
“…Comparisons with the pulsed-electric fi eld (PEF) method indicated that the decontamination effi ciency of the PWC method has been found to be slightly higher than that of the PEF method [26]. Atmospheric non-thermal plasma of the gliding-arc type (Glidarc) [27,28] has been found to be effi cient against microorganisms for treatments performed under burning discharge [29,30], and the inactivation of cells in water continued aft er the discharge had been switched off [29]. Microbial cells have been found to be killed by contact with water that had fi rst been activated by electric discharges (and so-called plasma-activated water [PAW]) without themselves being subjected to the plasma plume [31].…”
Section: Application Of Plasma For Water Purifi Cationmentioning
confidence: 99%